Association Between Red Blood Cell Distribution Width and COVID-19 Severity in Delta Variant SARS-CoV-2 Infection - Zhang, Jianguo; Hu, Jianhui; Huang, Xing; Fu, Shixiang; Ding, Daoyin; Tao, Zhimin (Frontiers in Medicine, 2022)
Studies have discovered that wild-type SARS-CoV-2 infections are commonly linked to abnormalities in hematological profiles of COVID-19 patients, one of them characterized by elevations in red blood cell distribution width (RDW). Whether this linkage reoccurs in delta variant SARS-CoV-2 infection remains unexamined. Here we compared baseline blood parameters in COVID-19 patients infected by wild type and its delta variant, respectively. Our results here point to that although delta variant has shown increased virulence, transmissibility, and vaccine escape, it has a minimally negative impact on RDW values that were previously found prognostic for COVID-19 severity.